Electrolyte composition having high viscosity and high long-term performance stability - LI CHUNHUA (2017)
The invention provides an electrolyte composition having high viscosity and high long-term performance stability. The electrolyte composition includes 3 to 6 wt% of sulfate, 5 to 9 wt% of inorganic acid or organic acid, 7 to 13 wt% of polyving akohol, 5 to 8 wt% of non-ionic surface active agent, 1.2 to 1.5 wt% of stability promoter, 30 to 40 wt% of non-aqueous solvent and 40 to 45 wt% of water. Aiming at a problem of how to keep long-term stable electrochemical performance of an electrolyte having high viscosity used for a flexible super capacitor in a current phase, the invention provides the electrolyte composition which is high in viscosity, high in conductivity, wide in electrochemical working window and stable in long-term performance. 本发明提供了种具有高粘度并且随时间保持性能稳定的电解质组合物，所述电解质组合物包括组分及含量如下：硫酸盐3～6wt％，无机酸或有机酸5～9wt％，聚乙烯醇7～13wt％，非离子表面活性剂5～8wt％，稳定助剂1.2～1.5wt％，非水溶剂30～40wt％，水40～45wt％。本发明是针对现阶段用于柔性超级电容器的高粘度电解质如何具备随时间保持稳定的电化学性能的问题，提出的种粘度大、电导率高、电化学工作窗口很宽并且性能随时间能够直保持稳定的电解质组合物。